PENGARUH ELEKTRODA GRAFIT-GRAFIT, ALMUNIUM-GRAFIT, DAN SENG-GRAFIT PADA ELEKTROLISIS KOBALT (Co2+ ) DENGAN PENGOTOR ION SENG (Zn2+ ) - Wulansari, Rismita (Chem Info Journal, 2013)
A study concerning about  taking cobalt metal (Co2+) has been done.  The metal  with  drawal  can  be  done  in  various  method  like  electrowinning  with electrolysis principle. This research purpose is to determine influence of electrode variation such as C-C, Al-C, and Zn-C toward precipitation of cobalt. Electrolysis cell is composed of graphite anode (C) and varieted cathode such as graphite (C), alluminium  (Al), and zinc (Zn). Sample was made content of  ion Co2+ and Zn2+ with  electrolyte  solution  such  as HCl  for  anode and without  electrolyte  solution for  cathode,  andthen  both  of  sample  was  connected  with  KCl  salt  bridge. Electrolysis was  done  in  2,8 Volt  during  40 minute with  various  electrode  pair such as C-C, Al-C, and Zn-C. Solution from electrolysis was analysed using AAS (Atomic Absorption Spectroscopy). The result from analysis showed the decreased of  Co2+ concentration  before  and  after  analysis.  For  electrolysis  without impurities,  the  concentration was decreased by 105 ppm  (C-C), 70 ppm  (Al-C), 2and  100  ppm  (Zn-C),  meanwhile  when  electrolysis  used  impurities,  the concentration was decreased by 85 ppm (C-C), 50 ppm (Al-C), and 70 ppm (Zn-C).  The  highest  yield  was  obtained  when  electrolysis  used  C-C  electrode  pair which  is  7,9%  for  electrolysis  without  impurities and  for  electrolysis  with impurities the result 6,3%. The highest efficiency was obtained when electrolysis used Al-C electrode pair which is 11,7% when electrolysis without impurities and Zn-C was 23,48%  when electrolysis with impurities